Processo biotecnológico voltado a produção de estoques poliploides do camarão-branco litopenaeus vannamei (decapoda, penaeidae) - Accioly, Ingrid Vilar (2013)
without practical results so far. Protocols used in biotechnological cultured aquatic organisms aimed at increasing growth rates and disease resistance, have been studied and perfected. Among the available techniques, the application of chromosomal manipulation, although still nascent, is presented as a tool aimed at mitigating ecological and economical issues in shrimp farming. The polyploidization artificial method already employed in fish and shellfish, has been widely researched for use in farmed shrimp. Some limitations of this method of expansion in shrimp refer to a better knowledge of cytogenetic aspects, the level of sexual dimorphism and performance in growing conditions. To contribute on some of these issues, the present study aimed to characterize cytogenetic species Litopenaeus vannamei (Decapoda) and Artemia franciscana (Anostraca), analyze the effectiveness of methods for detection of ploidy, through the use of flow cytometry in processes of induction polyploidy cold thermal shock at different stages of development of newly fertilized eggs. Additionally, aimed also the qualitative and quantitative comparison of larval development between diploid and polyploid organisms, besides the identification of sexual dimorphism in L. vannamei, through geometric morphometrics. The results provide information relevant to the improvement and widespread use of biotechnological methods applied toward national productivity in shrimp farming